The annual recurrence risk model for tailored surveillance strategy in patients with cervical cancer. (November 2021) - Cibula, David; Dostálek, Lukáš; Jarkovsky, Jiri; Mom, Constantijne H.; Lopez, Aldo; Falconer, Henrik; Fagotti, Anna; Ayhan, Ali; Kim, Sarah H.; Isla Ortiz, David; Klat, Jaroslav; Obermair, Andreas; et al.
Abstract: Purpose: Current guidelines for surveillance strategy in cervical cancer are rigid, recommending the same strategy for all survivors. The aim of this study was to develop a robust model allowing for individualised surveillance based on a patient's risk profile. Methods: Data of 4343 early-stage patients with cervical cancer treated between 2007 and 2016 were obtained from the international SCCAN (Surveillance in Cervical Cancer) consortium. The Cox proportional hazards model predicting disease-free survival (DFS) was developed and internally validated. The risk score, derived from regression coefficients of the model, stratified the cohort into significantly distinctive risk groups. On its basis, the annual recurrence risk model (ARRM) was calculated. Results: Five variables were included in the prognostic model: maximal pathologic tumour diameter; tumour histotype; grade; number of positive pelvic lymph nodes; and lymphovascular space invasion. Five risk groups significantly differing in prognosis were identified with a five-year DFS of 97.5%, 94.7%, 85.2% and 63.3% in increasing risk groups, whereas a two-year DFS in the highest risk group equalled 15.4%. Based on the ARRM, the annual recurrence risk in the lowest risk group was below 1% since the beginning of follow-up and declined below 1% at years three, four and >5 in the medium-risk groups. In the whole cohort, 26% of recurrences appeared at the first year of the follow-up, 48% by year two and 78% by year five. Conclusion: The ARRM represents a potent tool for tailoring the surveillance strategy in early-stage patients with cervical cancer based on the patient's risk status and respective annual recurrence risk. It can easily be used in routine clinical settings internationally. Highlights: The recurrence risk model in cervical cancer was composed of five prognostic factors. The developed annual recurrence risk model (ARRM) stratifies the cohort into five significantly distinctive risk groups. The ARRM represents a powerful tool for tailoring of appropriate surveillance strategy. The ARRM can easily be used in routine clinical settings internationally.